STUDI PENGARUH POSISI BUKAAN DINDING BATA PADA PORTAL - Medriosa, Hamdeni; Ridwan, Muhammad; AGUS, AGUS; Nofera, Wenda; Gustiani, Yusnita (Journal of Infrastructural in Civil Engineering, 2024)
Walls with brick filling are one of the building elements that separate and form rooms. The wall with brick filler is assumed only to be a load on the frame structure and does not consider the existence of this wall as structural. However, walls also have openings, which are essential for infill walls for functional reasons such as doors, windows, air circulation, and other building operations. These wall openings make predicting reinforced concrete structures' behavior and seismic capacity challenging. Numerical modeling and simulations have been conducted using software to evaluate the lateral strength of wall structures with openings as wide as 35% and several types of openings. The analysis results show that the strength of reinforced concrete structures with openings of 35% for type 1 is 93.21 kN, type 2 is 81.77 kN, and type 3 is 89.71 kN. It can be concluded that infill walls that have openings of 35% still contribute to resisting lateral loads because they do not exceed the specified standard deviation, namely 20%.